2013
DOI: 10.1074/jbc.m112.398503
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Maltosyltransferase GlgE, a Genetically Validated Antituberculosis Target, Is Negatively Regulated by Ser/Thr Phosphorylation

Abstract: GlgE is a maltosyltransferase involved in the biosynthesis of α-glucans that has been genetically validated as a potential therapeutic target against Mycobacterium tuberculosis. Despite also making α-glucan, the GlgC/GlgA glycogen pathway is distinct and allosterically regulated. We have used a combination of genetics and biochemistry to establish how the GlgE pathway is regulated. M. tuberculosis GlgE was phosphorylated specifically by the Ser/Thr protein kinase PknB in vitro on one serine and six threonine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 42 publications
2
41
0
Order By: Relevance
“…In agreement with the toxicity of maltose-1-phosphate as the basis of essentiality of GlgE and GlgB, prevention of maltose-1-phosphate formation through genetic or pharmacological inactivation of TreS allows deletion of both glgE and glgB in M. tuberculosis (23). Recently, it was demonstrated that GlgE activity can be negatively fine-tuned via phosphorylation by the serine/ threonine protein kinase PknB (72), although it is unclear if this regulation is important for M. tuberculosis virulence. Given the high toxicity of maltose-1-phosphate, its synthesis rate also needs to be subject to one or more regulatory mechanisms in order to balance production and consumption.…”
Section: Conversion Of Trehalose To Alpha-glucansmentioning
confidence: 85%
“…In agreement with the toxicity of maltose-1-phosphate as the basis of essentiality of GlgE and GlgB, prevention of maltose-1-phosphate formation through genetic or pharmacological inactivation of TreS allows deletion of both glgE and glgB in M. tuberculosis (23). Recently, it was demonstrated that GlgE activity can be negatively fine-tuned via phosphorylation by the serine/ threonine protein kinase PknB (72), although it is unclear if this regulation is important for M. tuberculosis virulence. Given the high toxicity of maltose-1-phosphate, its synthesis rate also needs to be subject to one or more regulatory mechanisms in order to balance production and consumption.…”
Section: Conversion Of Trehalose To Alpha-glucansmentioning
confidence: 85%
“…3,10 To further explore their commonalities, the M. tuberculosis enzyme was exposed to 2-deoxy-2-fluoro-α-maltosyl fluoride. MALDI-TOF MS identified an increase in mass of the intact protein of 324 Da, from 80316 Da (80316 Da, expected) to 80640 Da, consistent with formation of a covalent intermediate despite it being the wild-type protein rather than an active site mutein.…”
Section: Resultsmentioning
confidence: 99%
“…This is the only phosphorylase that is considered to be involved in the synthesis of glycoside. After the publication of this report, a series of reports considering the inhibitor of GlgE were published with the expectation that they may aid the development of a novel drug for multidrug-resistant strains of M. tuberculosis, the notorious pathogenic bacterium that causes tuberculosis (Kalscheuer et al 2010;Leiba et al 2013;Veleti et al 2014;Syson et al 2014;Sengupta et al 2014Sengupta et al , 2015. The 3D structure of the enzyme from Streptomyces coelicolor is available (Syson et al 2011).…”
Section: Gh13 Subfamilymentioning
confidence: 97%